Photonic and electronic properties of fluoride materials - Tressaud, Alain; Poeppelmeier, Kenneth Reinhard (Amsterdam Elsevier, 2016)
Photonic and Electronic Properties of Fluoride Materials: Progress in Fluorine Science, the first volume in this new Elsevier series, provides an overview of the important optical, magnetic, and non-linear properties of fluoride materials. Beginning with a brief review of relevant synthesis methods from single crystals to nanopowders, this volume offers valuable insight for inorganic chemistry and materials science researchers. Edited and written by leaders in the field, this book explores the practical aspects of working with these materials, presenting a large number of examples from inorganic fluorides in which the type of bonding occurring between fluorine and transition metals (either d- or 4f-series) give rise to peculiar properties in many fundamental and applicative domains. This one-of-a-kind resource also includes several chapters covering functional organic fluorides used in nano-electronics, in particular in liquid crystal devices, in organic light-emitting diodes, or in organic dyes for sensitized solar cells. The book describes major advances and breakthroughs achieved by the use of fluoride materials in important domains such as superconductivity, luminescence, laser properties, multiferroism, transport properties, and more recently, in fluoro-perovskite for dye-sensitized solar cells and inorganic fluoride materials for NLO, and supports future development in these varied and key areas. The book is edited by Alain Tressaud, past chair and founder of the CNRS French Fluorine Network. Each book in the collection includes the work of highly-respected volume editors and contributors from both academia and industry to bring valuable and varied content to this active field.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Fluorine -- Properties; Fluorine compounds; Electronic books